Experience of Violence from the Clients and Coping Methods Among Intensive Care Unit Nurses Working in a Hospital in South Korea - Hye Jin Yoo; Eunyoung E. Suh; Soon Haeng Lee; Jin Hee Hwang; Ji Hye Kwon (Elsevier, 2018)
Purpose: It is difficult to develop a good defense system that can prevent nurses from experiencing physical and verbal violence from patients and families in intensive care units, which are closed spaces. This study aimed to identify intensive care nurses' experience of violence from patients and families and investigate their coping methods, if there are any, in a tertiary hospital in South Korea. Methods: This study used a mixed methods design using both a survey for collecting quantitative data and individual interviews for a qualitative one. A total of 200 intensive care nurses participated in the survey, with 30 of them taking part in individual interviews. Survey data were analyzed using SPSS 21.0 program, and qualitative data were analyzed by qualitative content analysis method. Results: In the survey, 99.5% of the nurses reported that they had experienced violence from the patients, and 67.5% of the nurses reported that they had experienced violence from their visitors (families or relatives). Verbal violence were reported more than physical ones. They showed moderate or severe responses to violence, scoring an average of 2.98 ± 0.63 of 5. The qualitative data were analyzed to draw four themes, eight categories, and 17 subcategories. The four themes were perception of violence, coping with violence experience, coping resources, and caring mind after violence experience. Conclusion: While intensive care nurses experience unpredicted violence from patients and their visitors, they fail to cope well with the experience. The safe working environment of intensive care units is expected to contribute to quality care and an improvement of expertise in nursing. Keywords: family, intensive care units, nurses, patients, violence